Cancer pharmacology : an illustrated manual of anticancer drugs - Emadi, Ashkan; Karp, Judith E. (New York, NY : Springer Publishing Company, 2024)
"We are living in an exciting time for cancer pharmacology. The fusion of multiple disciplines of basic and clinical science is creating effective, life-prolonging therapies for a growing number of malignancies. The progress is electrifying and the promise for patients is exhilarating!"--
Drug Development in Oncology / Edward A. Sausville and Ashkan Emadi -- Pharmacogenomics / Milly Graveno -- Critical Components of Clinical Trials Development : From Bench to Bedside and Back / S. Percy Ivy, Richard F. Little, and Joshua F. Zeidner -- Drug Development and Regulatory Considerations / Vicky Hsu, Matthew D. Thompson, Donna Przepiorka, and Olanrewaju O. Okusanya -- Alkylating Agents / Ashkan Emadi and Edward A. Sausville -- Pyrimidine- and Purine-based Antimetabolites, Hydroxyurea, Asparaginases / Ashkan Emadi and Judith E. Karp -- Antimetabolites : Antifolates / Justin Lawson -- Antimitotics / Edward A. Sausville and Ashkan Emadi -- DNA Repair, Apoptotic Pathways, and CDK Inhibitors / Mira A. Kohorst and Scott H. Kaufmann -- Epigenetic Modulators / Sergiu Pasca and Lukasz P. Gondek -- Differentiating Agents and Microenvironment / Yuya Nagai and Gabriel Ghiaur -- Targeted Therapeutics (Small Molecules) / Yuchen (Jake) Liu and Ashkan Emadi -- Hormonal Therapies Alone and in Combinations for Treatment of Breast Cancer / Amy M. Fulton and Katherine H. R. Tkaczu -- Androgen Receptor Axis Targeting in the Treatment of Prostate Cancer / Vincent C. O. Njar and Arif Hussain -- Multiple Myeloma as a Paradigm for MultiTargeted Intervention / Kathryn Maples and Sagar Lonial -- Transplant-Related Agents : Focus on Graft vs. Host Disease Prevention and Treatment / Vedran Radojcic -- Monoclonal Antibodies Including Immunoconjugates, Antibody-Drug Conjugates, and Cytokine-Directed Agents / Alison Duffy and Ciera Bernhardi -- Immunotherapeutics : Immune Checkpoint Inhibitors, Vaccines, Bispecifics, and Engineered T Cells / Mark Yarchoan and Elizabeth Jaffee.
Includes bibliographical references and index.
PHR
Trim Education
Keywords: Antineoplastic Agents -- pharmacology; Neoplasms -- drug therapy; Molecular Targeted Therapy; Pharmacy